2018
DOI: 10.1111/jocn.14637
|View full text |Cite
|
Sign up to set email alerts
|

The effects of resilience and turnover intention on nurses’ burnout: Findings from a comparative cross‐sectional study

Abstract: The differences in nurse burnout and the effects of resilience and turnover intention on burnout should be better understood by nurse managers from Australia and China. Moreover, developing effective strategies relevant to their own country to reduce nurse burnout is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 60 publications
9
57
4
2
Order By: Relevance
“…One study involving 10,319 medical-surgical nurses of 303 hospitals in US, UK, Canada and Germany found an incidence of burnout ranging from 32% in Scotland to 54% in US (33). Also, it was reported that 20-40% of Australian nurses had burnout symptoms (34,35), while findings from another cross-sectional study showed that Australian nurses experienced higher burnout than their Chinese counterparts (36). Burnout among nurses has become a prevalent problem which needs to be taken seriously and addressed in both developed and developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…One study involving 10,319 medical-surgical nurses of 303 hospitals in US, UK, Canada and Germany found an incidence of burnout ranging from 32% in Scotland to 54% in US (33). Also, it was reported that 20-40% of Australian nurses had burnout symptoms (34,35), while findings from another cross-sectional study showed that Australian nurses experienced higher burnout than their Chinese counterparts (36). Burnout among nurses has become a prevalent problem which needs to be taken seriously and addressed in both developed and developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Social media has become ubiquitous in modern life and provides a large and readily available platform through which the public may receive information about nursing [ 30 ]. One way to enhance the public’s knowledge about nursing is through the use of social media [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on these considerations, the minimum sample size necessary to conduct the analysis was 82 in each sample (mentor/mentee). As noted previously, this sample size methodology, as well as the assumptions necessary to implement the methodology, has been used frequently in the literature (Faul et al, , Guo et al, ).…”
Section: Methodsmentioning
confidence: 99%